Pengaruh Problem Based Learning Terhadap Berpikir Kritis Siswa Pada Materi Ekosistem Kearifan Lokal - Ayu Nilna Li,izza DM; Mohammad Taufiq; Sri Hartatik; Nafiah Nafiah (Universitas Lampung, 2019)
The purpose of this study was to determine the influence of Problem Based Learning learning to students' critical thinking. The sample of this study was using 1 class with a total of 40 students, using a pre-experimental trial, One Group Pretest-Posttest. Data collection technique used was pretest and posttest test method. To find out the influence can be proven by testing using the Wilcoxon Matched Pairs test Based on the output of